Strategi Pemasaran untuk Membangun School Branding dalam Upaya Meningkatkan Daya Saing Lembaga Pendidikan di MA NU Sunan Giri Prigen KAB. Pasuruan - Indah, Nur Hasanah; Rahmania, Anisa; Magfiroh, Enik; Qoyim, Ahmad Nofahul; Ilham, Ahmad Ferdi Ari (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Technological advancements and social changes necessitate innovation in Indonesia's education system, including madrasas. This study focuses on the branding strategies employed by MA NU Sunan Giri Prigen in Pasuruan Regency to enhance its competitiveness. Utilizing qualitative methods through literature review and interviews, the research explores how MA NU Sunan Giri Prigen develops a strong identity, emphasizes core values, builds community relationships, and leverages social media and technology to strengthen its school brand.The findings indicate that MA NU Sunan Giri Prigen successfully establishes a strong brand identity through consistent use of logos, slogans, and school colors, while highlighting academic and non-academic excellence. The school actively participates in social activities and collaborates with the local community to reinforce its image as a quality educational institution relevant to the job market. This effective branding strategy has proven to enhance the school's reputation, attract new students, and strengthen alumni loyalty, enabling MA NU Sunan Giri Prigen to remain competitive in the increasingly challenging educational landscape.